Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 10: Infinite Sequences and Series - Section 10.9 - Convergence of Taylor Series - Exercises 10.9 - Page 625: 17


$1+\Sigma_{n=1}^\infty (-1)^n\dfrac{ 2^{(2n-1)}x^{(2n)}}{(2n)!}$

Work Step by Step

Consider the Maclaurin Series for $\cos x$ is defined as: $ \cos x=1-\dfrac{x^2}{2!}+\dfrac{x^4}{4!}-\dfrac{x^6}{6!}+...$ Use formula such as: $1+\cos 2x=2 \cos^2 x$ Then, we have $\cos^2 x=\dfrac{1}{2}+\dfrac{\cos 2x}{2}=\dfrac{1}{2}+1-\dfrac{(2x)^2}{2!}+\dfrac{(2x)^4}{4!}-\dfrac{(2x)^6}{6!}+...$ $\implies 1+\Sigma_{n=1}^\infty (-1)^n\dfrac{ 2^{(2n-1)}x^{(2n)}}{(2n)!}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.